Experimental investigation on flow and heat transfer characteristics of lead–bismuth eutectic in circular tubes. (5th November 2020) - Zhang, Yan; Wang, Chenglong; Cai, Rong; Lan, Zhike; Shen, Yaou; Zhang, Dalin; Tian, Wenxi; Su, Guanghui; Qiu, Suizheng
Highlights: Flow and heat transfer characteristics of LBE in circular tubes are studied. The frictional resistance coefficient of LBE in pipes is higher than water. The effects of heat flux, Re and diameter on the Nu of LBE and sodium were compared. New correlations for the frictional coefficient and Nu number were developed. Abstract: Flow and heat transfer characteristics of LBE are of significant importance for the thermal-hydraulic and safety analysis of lead-based fast reactors (LFRs). In this paper, an experimental research on the flow and heat transfer of LBE in tubes was carried out. Two test sections with different inner diameters of 20 mm and 35 mm were used. The test sections were uniformly heated with the heat flux ranging from 20 to 60 kW/m 2 . The Reynolds number ( Re ) in the experiment ranges from 38, 000 to 185, 000 and the Peclect number ( Pe ) ranges from 350 to 3800. The frictional resistance coefficient and heat transfer coefficient of LBE were obtained and corresponding correlations with respect to the dimensionless number were fitted. The effects of heat flux, Re and inner diameter of the test section on the heat transfer coefficients are investigated separately and the conclusion is compared with Na. Experimental results show that the frictional resistance coefficient of LBE is higher than that of water because of the different physical properties and test conditions. Based on the experimental results, a new heat transfer correlation of LBE in circular tubes is proposed: Nu = 3.8472 + 0.0179 P e 0.8037 . The correlation is appropriate for the prediction of Nu for higher Pe and gives slightly lower prediction in the low Pe region compared with the existing correlations. This paper provides important experimental support for the thermal-hydraulic analysis and design of LFRs.